2020
DOI: 10.3126/njz.v4i1.30668
|View full text |Cite
|
Sign up to set email alerts
|

Prey quantity affects development, survival and reproductive attributes of Coccinella transversalis Fabricius, 1781 under laboratory conditions

Abstract: This study assessed development, survival and reproductive parameters of a ladybird beetle, Coccinella transversalis Fabricius, 1781 on different quantities (viz. scarce, optimum and abundant) of the bean aphid prey, Aphis craccivora under laboratory conditions (27 ±1°C; 65 ±5% relative humidity and 14 light: 10 dark hours photoperiod). The pre-oviposition period was the shortest (6.40 ±0.40 days) on abundant prey and longest (9.20±0.49 days) on scarce prey. The oviposition period significantly increased with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
1
Order By: Relevance
“…It was found that present studies were varied with the findings of Gurung et al (2018) who reported the incubation period of 5.2± 1.28 days of C. transversalis on mustard aphid, L. erysimi. The hatching percentage of C. transversalis was found to be 67.85 to 97.43 with an average of 84.73± 8.114% in the present studies, while Bista (2020) reported that when the food is scarce the hatching % was 82.72± 0.67% and with optimum availability of food it goes up to 89.87± 0.87%. The period of first instar grub was in range of 2 to 4 with an average of 2.60± 0.638 days in the present studies.…”
Section: Resultscontrasting
confidence: 43%
“…It was found that present studies were varied with the findings of Gurung et al (2018) who reported the incubation period of 5.2± 1.28 days of C. transversalis on mustard aphid, L. erysimi. The hatching percentage of C. transversalis was found to be 67.85 to 97.43 with an average of 84.73± 8.114% in the present studies, while Bista (2020) reported that when the food is scarce the hatching % was 82.72± 0.67% and with optimum availability of food it goes up to 89.87± 0.87%. The period of first instar grub was in range of 2 to 4 with an average of 2.60± 0.638 days in the present studies.…”
Section: Resultscontrasting
confidence: 43%